Short- and long-run effects of external interventions on trust - Igor Asanov; Simone Vannuccini (Friedrich Schiller University Jena, 2015)
We experimentally analyze the effects of external interventions such as subsidy and targeting on investment decisions during the intervention and after. We employ a multi-period version of the trust (investment) game (Berg et al., 1995) introducing either the monetary incentives for contribution or providing a suggestion about the level of investment. The results of the experiment indicate that targeting is an effective instrument to promote trustful behavior, whereas subsidy policy is not effective both in short- and long-run. Therefore we suggest considering a targeting policy as one of the instruments that can foster trustful behavior.
Keywords: C92; L50; D80; 330; academic spin-offs; experiment; policy; subsidy; trust game